PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS PBL BERBANTUAN VR DENGAN DELIGHTEX UNTUK MENINGKATKAN LITERASI NUMERASI SISWA SMP N 1 SIANTAR - Fernando Purba; Mangaratua Marianus Simanjorang (JURNAL PEMBELAJARAN DAN MATEMATIKA SIGMA (JPMS), 2026)
This study aims to improve the numeracy literacy abilities of students who are still relatively low. In addition, the use of Delightex Edu media, which had never been used in the learning process at SMP Negeri 1 Siantar, makes the developed media a new innovation in mathematics learning at the school, especially to enhance students' numeracy literacy. This research is a development study involving 27 students of class VII-1 at SMP Negeri 1 Siantar. The research instruments consist of expert validation questionnaires, student practicality questionnaires, learning implementation observation sheets, two numeracy literacy tests, and student response questionnaires that have been validated. The analysis results showed that 1) the media expert validation achieved an average of 90.66%, and the content expert validation reached an average of 89.43%. 2) The results of the analysis of the student practicality questionnaire towards the media reached a percentage of 86.77%, and the analysis of the observation sheets on the implementation of learning reached an average of 86.95%. 3) The results of the classical completeness analysis reached a percentage of 85.18% with the number of students achieving complete scores being 24 students, and the results of the student response questionnaire analysis reached a percentage of 94.08%. 4) The N-Gain score as an improvement in students' numeracy literacy obtained was 0.60, which falls into the medium category, with details of 15 students in the medium category, 9 students in the high category, 2 students in the low category, and 1 student did not experience improvement. Thus, this learning media is feasible, practical, and effective to use in mathematics learning in the classroom.